81P Efficacy of weekly paclitaxel-bevacizumab combination in advanced non squamous non-small cell lung cancer (NSCLC) progressing after immune checkpoint inhibitors - AVATAX, a retrospective multicentric study: Preliminary data. (15th December 2019) - Valery, S C; Chouaid, C; Rousseau-Bussac, G; Monnet, I; Bilger, G; Boré, P; Pinsolle, J; Descourt, R; Geier, M; Toffart, A C; Cony-Makhoul, P; Robinet, G; et al.
Abstract: Background: ULTIMATE, a phase III trial, showed a significant superiority regarding progression free survival (PFS) of the combination paclitaxel-bevacizumab versus docetaxel as second or third line treatment for advanced non-small cell lung cancer (NSCLC). With the increase use of immunotherapy in ﬁrst-line setting, second line strategies must be redefined. Paclitaxel-bevacizumab combination could be an option. Methods: The main objectives were to describe safety and efficacy of this combination in metastatic non-squamous NSCLC as second-line therapy or beyond with a special attention paid to the sub-group treated just after immune checkpoint inhibitors. It was a multicentric retrospective study. Results: This analysis included from 1st September 2010 to 1st april 2018, 76 patients: 42 (55%) male, 18 (24%) and 36 (47%) treated in second and third line respectively, and 22 (29%) in fourth line or more. Overall response rate (ORR) was 37% (28/76) and disease control rate 74 % (56/76). Median PFS and OS were 5, 7 [95%CI: 4, 1-6, 9] months and 11, 2 [95%CI: 8-not reached] months respectively. In second and third line, ORR was respectively 39% and 42%, PFS 4 months [95%CI: 2, 5-7, 7] and 6 months [95%CI: 4-7], OS 9, 4 months [95%CI: 2, 7-not reached] and was not reached in third line at 12 months. Grade 3–4 adverse events included asthenia 5% (4/76), neurotoxicity 3% (2/76), bleeding events 4% (3/76), and hematological toxicity 1% (1/76). In the subset of patients treated in third-line or beyond, immediately after immunotherapy (33/76), we note with interest that ORR was 42% (14/33), median PFS was 6, 2 [95% CI: 4, 6-7, 7] months, and median overall survival was not reached at 12 months. Conclusion: This study shows an acceptable toxicity profile associated with encouraging efficacy of the combination paclitaxel-bevacizumab as second-line treatment or beyond for non –squamous NSCLC patients. Moreover, these results seems to be very promising preliminary findings for patients treated just after immunotherapy. AVATAX is ongoing and should collect data from about 200 patients. Legal entity responsible for the study: Chantal Decroisette. Funding: Has not received any funding. Disclosure: C. Chouaid: Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: AZ; Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: BI; Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Bayer and Amgen; Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Takeda; Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Pfizer; Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Novartis; Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Lilly; Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: MSD; Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Bristol-Myers Squibb; Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Sanofi Aventis; Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Speaker Bureau / Expert testimony, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: GSK. G. Rousseau-Bussac: Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self): roche; Travel / Accommodation / Expenses: Bristol-Myers-Squibb, Travel / Accommodation / Expenses: Takeda; Travel / Accommodation / Expenses: Roche; Travel / Accommodation / Expenses: Pfizer; Travel / Accommodation / Expenses: Novartis; Travel / Accommodation / Expenses: MSD; Travel / Accommodation / Expenses: Mundipharma; Travel / Accommodation / Expenses: Lilly; Travel / Accommodation / Expenses: Janssen-Cilag; Travel / Accommodation / Expenses: Boehringer Ingelheim. J. Pinsolle: Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: MSD; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Takeda; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Pfizer; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Roche; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Pierre Fabre. R. Descourt: Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Boehringer Ingelheim; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Pfizer; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Roche; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Bristol-Myers Squibb; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: MSD; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: AstraZeneca; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Takeda. M. Geier: Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: MSD; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Bristol-Myers Squibb. C. Decroisette: Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Pfizer; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Takeda; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Boehringer Ingelheim; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: AstraZeneca; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: MSD; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Bristol-Myers Squibb. All other authors have declared no conflicts of interest.